What Is a Translation? - Alex Brotherton (Journal of Modern Languages)
The present study considers the diversity of definitions of translation presented in numerous books and articles during the last thirty years, which reveals a wide difference of opinion both on the nature of translation and on methods of translating, but also reflects a certain convergence towards a systematic approach to theory and practice. The definition of Nida (1959) of translation is considered as one of the most frequently quoted definitions of translation here.